2016
DOI: 10.1542/peds.2015-2475
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Illness and Developmental Vulnerability at School Entry

Abstract: OBJECTIVE: This study examined the association between chronic illness and school readiness, by using linked administrative population data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 32 publications
1
53
0
5
Order By: Relevance
“…Defining sarcopenia without assessing muscle function is not optimum, as muscle strength is not linearly related to muscle mass . Reduced muscle function may be directly impacted by delays in fine motor, gross motor, and cognitive development in early childhood or vice versa, especially in children with chronic diseases . There is currently no gold standard tool to assess motor function impairment in children being assessed for sarcopenia .…”
Section: Discussionmentioning
confidence: 99%
“…Defining sarcopenia without assessing muscle function is not optimum, as muscle strength is not linearly related to muscle mass . Reduced muscle function may be directly impacted by delays in fine motor, gross motor, and cognitive development in early childhood or vice versa, especially in children with chronic diseases . There is currently no gold standard tool to assess motor function impairment in children being assessed for sarcopenia .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that children who experience chronic illness are at risk of developmental vulnerability 28. Child chronic illness diagnoses (corresponding to the list used by Bell and colleagues28) were therefore identified to account for intergenerational health disadvantage.…”
Section: Methodsmentioning
confidence: 99%
“…Child chronic illness diagnoses (corresponding to the list used by Bell and colleagues28) were therefore identified to account for intergenerational health disadvantage. Child diagnoses were identified from the same datasets as parent diagnoses, from birth until the end of 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Children are particularly vulnerable to complications of chronic disease, and symptoms of severe acute complications can often be missed in these patients . Central venous catheter (CVC)‐related complications can be life‐threatening, with an estimated 12.5%–25% mortality associated with catheter‐related bloodstream infections (CRBSIs) .…”
Section: Introductionmentioning
confidence: 99%